Inovasi Model Pembelajaran Bahasa Indonesia untuk Meningkatkan Keterampilan Literasi Siswa Sekolah Menengah - Insan, Al; Rusmaniar, Rusmaniar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2025)
The low literacy skills of Indonesian secondary school students, as reflected in the results of PISA 2018, indicate the need for more innovative learning strategies that are relevant to technological developments. This study aims to analyze innovative Indonesian language learning models that can enhance the literacy skills of secondary school students, particularly at the junior high school level. The method employed is a descriptive qualitative approach using a literature review method, examining research findings from the past five years published in nationally accredited journals and scientific proceedings. The findings show that innovative learning models such as Project-Based Learning, Problem-Based Learning, digital-based literacy, and collaborative learning have proven effective in improving students’ reading, writing, critical thinking, and communication skills. Moreover, the successful implementation of these models is influenced by teacher readiness, infrastructure availability, and school policy support.